(7x+6)+(5x+3)=90

Simple and best practice solution for (7x+6)+(5x+3)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x+6)+(5x+3)=90 equation:


Simplifying
(7x + 6) + (5x + 3) = 90

Reorder the terms:
(6 + 7x) + (5x + 3) = 90

Remove parenthesis around (6 + 7x)
6 + 7x + (5x + 3) = 90

Reorder the terms:
6 + 7x + (3 + 5x) = 90

Remove parenthesis around (3 + 5x)
6 + 7x + 3 + 5x = 90

Reorder the terms:
6 + 3 + 7x + 5x = 90

Combine like terms: 6 + 3 = 9
9 + 7x + 5x = 90

Combine like terms: 7x + 5x = 12x
9 + 12x = 90

Solving
9 + 12x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 12x = 90 + -9

Combine like terms: 9 + -9 = 0
0 + 12x = 90 + -9
12x = 90 + -9

Combine like terms: 90 + -9 = 81
12x = 81

Divide each side by '12'.
x = 6.75

Simplifying
x = 6.75

See similar equations:

| 7=3+k | | 74-60x=300 | | -2h=-18 | | 6+5x=-4x+57 | | c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 | | 2m-(x+2)=0 | | log4x=5/2 | | (X+2y)(x^3-2x^2y+4xy^2)= | | 3-1/2x=-5 | | 4x=-7y-37 | | 9x-3+2x+20=15+4x+2+7x | | 2x+17-7x-6=8-10x-19+5x | | (5x+3)2y=43 | | 5(3x+3)-5x=95 | | (3x-6)+(5x+9)= | | (7x+2)2= | | (7/9)+(5/6)=x | | 4a+7b=43 | | (4/9)-(1/2)=x | | 5s+20=150 | | x+.8x=25 | | 44=5x-4 | | X+2x=145 |

Equations solver categories